Electrospray and MALDI mass spectrometry : fundamentals, instrumentation, practicalities, and biological applications - Cole, Richard B. , 1956- (John Wiley & Sons, 2010)
Electrospray Mass Spectrometry: Fundamentals, Instrumentation, and Applications, Second Edition is an extensively updated version of the original guide